PROFIL TERAPI OBAT PADA PASIEN RAWAT INAP DENGAN DIARE AKUT PADA ANAK DI RUMAH SAKIT UMUM NEGARA - Arifani Siswidiasari; Ketut Widyani Astuti; Sagung Chandra Yowani (Jurnal Kimia (Journal of Chemistry), 2014)
The Diarrhea in children is the highest cause of morbidity and mortality in the world, especially in the developing countries. The purposes of this research are to describe about patient profile, the use of medicines profile and the treatment period in the RSU Negara. The research method used was a descriptive retrospective by taking medical records of childhood diarrhea patients in The Public Hospital RSU Negara  from July to December 2012. The diarrhea type studied was acute diarrhea in children  in age range of 0-14 years. The results showed that the drugs which were used for the acute diarrhea treatment in the Public Hospital of RSU Negara were: male (69.57%), female (30.43%), with age range: 0 - <1 year old (60.87%), 1 - <5 years old (34.78%), and 5 - <14 years old (4.35%). The highest classification of acute diarrhea were acute diarrhea with mild dehydration (63.04%) and without dehydration (36.96%). The use of antibiotics (89.13%), without antibiotics (10.87%), the use of ringer's lactate (93.48%), dextrose (13.04%), zinc (65.22%), antiemetic (58.69%), antipyretic (54.35 %), antacids (2.17%), H2 blocker (23.91%), probiotics (21.74%), synbiotics (34.78%), ORS (10.87%), dexamethasone (4.35%), dygestive enzymes (2.17%), nystatin (2.17%). The condition of diarrhea patient when they were released from the hospital were cured (67.39%), begins to be cured (32.61%), with various of  treatment duration from  3 days (69.57%) , 4 days (23.91%), and 5 days (6.52%).